Synthesis of all-aliphatic polyamide dendrimers based on a 3,3′-diaminopivalic acid scaffold. - Ruiz-Sánchez, Antonio Jesús; Mesa-Antúnez, Pablo; Barbero, Nekane; Collado-Martín, Daniel; Vida-Pol, Yolanda; Nájera-Albendín, Francisco; Pérez-de-Inestrosa-Villatoro, Ezequiel (RSC publication, 2015)
Over recent years the importance of dendrimers has continued to increase in both life and material sciences. Multiple chemical strategies have been described toward the preparation of dendrimeric structures. Here, we present a new approach for the production of all-aliphatic polyamide dendrimers. In our approach, iterative 3,3′-diaminopivalic acid connections act as building blocks for dendrimer construction. 3,3′-Diazidopivalic acid units underpin a two-step pathway involving carboxylic acid–amine condensation, followed by azide reduction. The carboxylic acid–amine condensation step can be carried out by conventional methods, while the hydrogen-catalyzed azide-to-amine reduction is a clean process particularly appropriate for dendrimer preparation. Spectroscopic characterization of functionalized surface azides (Gn-N3) and amines (Gn-NH2) confirm the proposed structures. These dendrimers were studied in explicit solvent by atomistic forcefield-based molecular dynamics to characterize structural properties such as shape, radius and monomer distribution. Our results show that these compounds are similar in size and shape, with Gn-NH2 having a slightly bigger size and exhibiting lower terminal unit backfolding.
Keywords: Dendrímeros; Poliamidas; 3,3′-diaminopivalic acid; Dendrimer; All-aliphatic polyamide